2021
DOI: 10.1080/15548627.2021.1886839
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel lipid droplet factors that regulate lipophagy and cholesterol efflux in macrophage foam cells

Abstract: Macrophage autophagy is a highly anti-atherogenic process that promotes the catabolism of cytosolic lipid droplets (LDs) to maintain cellular lipid homeostasis. Selective autophagy relies on tags such as ubiquitin and a set of selectivity factors including selective autophagy receptors (SARs) to label specific cargo for degradation. Originally described in yeast cells, “lipophagy” refers to the degradation of LDs by autophagy. Yet, how LDs are targeted for autophagy is poorly defined. Here, we employed mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 99 publications
5
79
0
Order By: Relevance
“…Macrophages can reduce excessive lipid accumulation in the body by increasing the lipolysis of intracellular LDs, avoiding damage to cells from lipid toxicity and alleviating the further development of atherosclerosis. The primary mechanisms include the miR-328-5p reduction-mediated histone deacetylase 3/ATP-binding cassette transporter A1 pathway ( Huang et al, 2021 ), lipid droplet ubiquitination mediated by AUP1 ( Robichaud et al, 2021 ), TAG synthesis guided by GPAT3 and GPAT4 ( Quiroga et al, 2021 ), hydrolysis of cholesterol ester catalyzed by neutral cholesterol ester hydrolase 1 ( Matsuoka et al, 2020 ), Foxc2-induced Angptl2-mediated lipid accumulation ( Yang L. et al, 2020 ), inhibition of mitochondrial respiration by iNOS-derived nitric oxide ( Rosas-Ballina et al, 2020 ), SphK2-affected lipid droplet decomposition mediated by autophagosomes and lysosome ( Ishimaru et al, 2019 ), BECN1 and ATG14 mediated autophagy ( Singh et al, 2009 ; Ouimet et al, 2011 ; Hadadi-Bechor et al, 2019 ), lipid accumulation marked by the perilipin family of PLIN1-PLIN5 ( Sztalryd and Brasaemle, 2017 ; Bosch et al, 2020 ), LD biogenesis mediated by PPAR signaling pathway ( Yang T. et al, 2020 ), acute iron deprivation ( Pereira et al, 2019 ), neutral lipase-mediated hydrolysis of neutral fat in LDs ( van Dierendonck et al, 2020 ), and fat phagocytosis mediated by Hmgb1, Hmgb2, Hspa5 and Scarb2 ( Robichaud et al, 2021 ; Figure 4 ). HILPDA is a physiological inhibitor of ATGL-mediated lipolysis in macrophages that binds to the intracellular triglyceride hydrolase ATGL and inhibits ATGL-mediated triglyceride hydrolysis ( van Dierendonck et al, 2020 ).…”
Section: Lipid Droplets and Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages can reduce excessive lipid accumulation in the body by increasing the lipolysis of intracellular LDs, avoiding damage to cells from lipid toxicity and alleviating the further development of atherosclerosis. The primary mechanisms include the miR-328-5p reduction-mediated histone deacetylase 3/ATP-binding cassette transporter A1 pathway ( Huang et al, 2021 ), lipid droplet ubiquitination mediated by AUP1 ( Robichaud et al, 2021 ), TAG synthesis guided by GPAT3 and GPAT4 ( Quiroga et al, 2021 ), hydrolysis of cholesterol ester catalyzed by neutral cholesterol ester hydrolase 1 ( Matsuoka et al, 2020 ), Foxc2-induced Angptl2-mediated lipid accumulation ( Yang L. et al, 2020 ), inhibition of mitochondrial respiration by iNOS-derived nitric oxide ( Rosas-Ballina et al, 2020 ), SphK2-affected lipid droplet decomposition mediated by autophagosomes and lysosome ( Ishimaru et al, 2019 ), BECN1 and ATG14 mediated autophagy ( Singh et al, 2009 ; Ouimet et al, 2011 ; Hadadi-Bechor et al, 2019 ), lipid accumulation marked by the perilipin family of PLIN1-PLIN5 ( Sztalryd and Brasaemle, 2017 ; Bosch et al, 2020 ), LD biogenesis mediated by PPAR signaling pathway ( Yang T. et al, 2020 ), acute iron deprivation ( Pereira et al, 2019 ), neutral lipase-mediated hydrolysis of neutral fat in LDs ( van Dierendonck et al, 2020 ), and fat phagocytosis mediated by Hmgb1, Hmgb2, Hspa5 and Scarb2 ( Robichaud et al, 2021 ; Figure 4 ). HILPDA is a physiological inhibitor of ATGL-mediated lipolysis in macrophages that binds to the intracellular triglyceride hydrolase ATGL and inhibits ATGL-mediated triglyceride hydrolysis ( van Dierendonck et al, 2020 ).…”
Section: Lipid Droplets and Immune Cellsmentioning
confidence: 99%
“…The LD-related proteins Perilipin 2 (PLIN2) and Perilipin 3 (PLIN3) are autophagic substrates that undergo autophagy degradation before lipolysis ( Kaushik and Cuervo, 2015 ). It was found that a decrease in autophagy promotes lipid accumulation and further inhibits autophagy, increasing lipid retention ( Robichaud et al, 2021 ). Lysosomes do not directly fuse with LDs but with autophagosomes containing LDs ( Singh, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy of macrophages play an anti-atherosclerotic effect by inhibiting the formation of foam cells and eliminating inflammation ( Wang Z. et al, 2020 ; Tao et al, 2021 ). Also, autophagy promotes the transformation of foam cells into alternately activated macrophages to alleviate late-stage atherosclerosis ( Robichaud et al, 2021 ). When autophagy is dysregulated, inflammasomes will be overactivated and promote the development of atherosclerosis ( Razani et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This model is supported by spartin's ability to bind LDs as well as LC3A/C, core components of the autophagy machinery and is consistent with the effect of spartin deficiency in cells, where it leads to accumulation of LDs and TGs. Whether additional lipophagy receptors exist for different cell types or different metabolic conditions is unknown, but remains an area of active investigation (35). The current findings show that the spartin-mediated lipophagy pathway may be important in neurons where its impairment leads to accumulation of LDs.…”
Section: Introductionmentioning
confidence: 70%